Revision of the treehopper genus Gelastogonia Kirkaldy, 1904 (Hemiptera, Membracidae) with description of new species from Ecuador and Colombia - Montalvo-Salazar, Jorge L.; Rueda-Rodríguez, María P.; López-García, Margarita M.; Flórez-V, Camilo (Zootaxa, 2026)
We present a taxonomic revision of the Andean treehopper genus Gelastogonia Kirkaldy, 1904. After reviewing all the type material of the genus, we transfer Gelastogonia parva Sakakibara to Ennya parva (Sakakibara) comb. nov. and designate a Lectotype for Gelastogonia bicristata (Stål). The genus is redescribed, along with the species Gelastogonia bicristata, Gelastogonia pulchella (Funkhouser), and Gelastogonia rufipes (Fairmaire) for which new distributional records are also provided. Additionally, sexual dimorphism is reported in the genus for the first time. Three new species are described from Ecuador: Gelastogonia andyi sp. nov. Montalvo-Salazar, Rueda-Rodríguez & López-García from the Subandean mountain range Cordillera del Cóndor, Gelastogonia cosanga sp. nov. Montalvo-Salazar, Rueda-Rodríguez & López-García from the Quijos Valley in the northeastern Andes, and Gelastogonia tandayapa sp. nov. Montalvo-Salazar, Rueda-Rodríguez & López-García from the northwestern Andes. Two new species are described from Colombia: Gelastogonia nubicola sp. nov. Flórez-V from the northern of the Cordillera Central and the Cordillera Occidental, and Gelastogonia xanthonota sp. nov. Flórez-V from the PNN Los Nevados. Keys to species for males and females, illustrations of each species, and distributional maps are provided.